Role of the aryl hydrocarbon receptor in tobacco smoke extract–induced matrix metalloproteinase‐1 expression. Issue 5 (25th April 2013) - Ono, Yuko; Torii, Kan; Fritsche, Ellen; Shintani, Yoichi; Nishida, Emi; Nakamura, Motoki; Shirakata, Yuji; Haarmann‐Stemmann, Thomas; Abel, Josef; Krutmann, Jean; Morita, Akimichi
Abstract: Findings from large epidemiologic studies indicate that there is a link between smoking and extrinsic skin ageing. We previously reported that matrix metalloproteinases (MMPs) mediate connective tissue damage in skin exposed to tobacco smoke extracts. Tobacco smoke contains more than 3800 constituents, including numerous water‐insoluble polycyclic aromatic hydrocarbons (PAHs) that trigger aryl hydrocarbon receptor (AhR) signalling pathways. To analyse the molecular mechanisms involved in tobacco smoke–induced skin ageing, we exposed primary human fibroblasts and keratinocytes to tobacco smoke extracts. Hexane‐ and water‐soluble tobacco smoke extracts significantly induced MMP‐1 mRNA in both human cultured fibroblasts and keratinocytes in a dose‐dependent manner. To clarify the involvement of the AhR pathway, we used a stable AhR‐knockdown HaCaT cell line. AhR knockdown abolished the increased transcription of the AhR‐dependent genes CYP1A1/CYP1B1 and MMP‐1 induced by either of the tobacco smoke extracts. Furthermore, the tobacco smoke extracts induced 7‐ethoxyresorufin‐O‐deethylase activity, which was almost completely abolished by AhR knockdown. Likewise, treating fibroblasts with AhR pathway inhibitors, that is, the flavonoids 3‐methoxy‐4‐nitroflavone and α‐naphthoflavone, blocked the expression of CYP1B1 and MMP‐1. These findings suggest that the tobacco smoke extracts induce MMP‐1 expression in human fibroblasts and keratinocytes via activation of the AhR pathway. Thus, the AhR pathway may be pathogenetically involved in extrinsic skin ageing.